Patient Satisfaction and Associated Factors Following Lumbar Disc Surgery - Cirkelė, Indrė; Rimaitis, Marius (Slauga. Mokslas ir praktika, 2024)
Patient satisfaction with medical services, including anesthesia, can help assess the quality of a functioning healthcare system and identify areas for improvement. Aim. We evaluated patient satisfaction with spinal and general anesthesia following lumbar disc surgery. Methods. An anonymous questionnaire survey was conducted between January – July 2023. The questionnaire included demographic information, pain levels, discomfort in the perioperative period, and patient satisfaction with anesthesia (numeric scale from 0 to 10). Results. In total, 119 men and 104 women participated in the study. Most patients were classified as ASA class II. Nearly half of the patients (43.4%) experienced symptoms of lumbar disc hernia more than 12 months ago. Analgesics were administered immediately postoperatively to 18% of subjects who underwent general anesthesia and 6.5% of those under regional anesthesia. Pain after surgery was more commonly reported by patients after regional anesthesia. Patients were most satisfied with the benevolence/caring of the operating room staff (9.86/10) and the least satisfied with pain relief in the incision area (9.43/10). A negative correlation was observed between the pain levels on the first and second day post-surgery and patient satisfaction with anesthesia (p < 0.05). Conclusions. Overall, patient satisfaction with anesthesia was very high (> 9 points out of 10), however, as pain level increase, patient satisfaction decreases (p < 0.05).